Edukasi Literasi Kesehatan Reproduksi tentang Manajemen Preventif Leukorhea pada Santriwati: Reproductive Health Literacy Education about Preventive Management of Leukorrhea in Female Students - Kurniati, Yuni Prastyo; Romadhon, Yusuf Alam; Futana, Ninda Pradani; Rosyita, Fadhilla Jihan; Farma, Aufa Faza Fauzan; Latifah, Lisanul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Teenager is an age group that is in a transitional period of human development. The transition period is the process of biological maturation into adults who can reproduce sexually and has the potential for all the consequences of sexual activity. Vaginal discharge is a problem that is often encountered after women experience puberty and may indicate a normal phenomenon, an infection, or other conditions. Healthy, clean-living behavior related to reproductive health in teenagers has a significant correlation with the level of knowledge and daily behavior of teenagers that affect leukorrhea. To increase the awareness of female students at the Modern Assalam Islamic Boarding School regarding clean and healthy living behavior in the field of healthy female reproduction system with support from health professionals and preventive education on leucorrhoea. This service activity was conducted with a total of 60 participants who were involved in filling out the pretest and post-test. The activity phase included initial studies through student-teacher discussions, preparation of learning materials and evaluation methods, and implementation of learning activities and evaluations. A total of 60 female students who took part in this reproductive health education activity got a preventive education knowledge, proved by comparing the pretest scores before the health education activity was carried out and the post-test after the educational activity. A significant increase was obtained with a rate of 93%. Activities related to leucorrhoea in female students show the effectiveness of significant improvement in the knowledge and enthusiasm of the participants.